EnergySaving Lighting of Agricultural Premises and its Parameters Calculation - L. Yu. Yuferev (Сельскохозяйственные машины и технологии)
he properly selected lighting for livestock farms is noted to ensure the optimal productivity of bred animals and poultry and to generate profit for the enterprise. (Research purpose) The research purpose is to substantiate the parameters of energy-saving lighting for agricultural premises and to develop methods for its calculation. (Materials and methods)  It has been shown that greenhouse farms most often use high and low pressure sodium lamps for lighting, but their spectrum only partially substitutes the natural one. It has been assumed that expanding the spectrum and approximating it to the solar one could improve product quality and yield. It has been stated that incandescent and fluorescent lamps are traditionally used to illuminate livestock and poultry premises, but they cannot create a lighting system with a «dawn - sunset» function, and their spectrum does not correspond to the full range perceived by animals and birds. It has been noted that the LED light sources’ functioning has such features that make the application of standard calculation methods impossible. We obtained formulas for calculating the light level and flux of photons. (Results and discussion) We provided examples of applying the energy-saving lighting systems developed by us in poultry houses with floor housing system, in cowsheds with tethered housing system and in an experimental phyto-laboratory for growing seedlings. It has been found that after replacing the lighting system based on DRL-125 lamps with a new one, with 36 nine-watt LED lamps, the power consumption decreased from 2,250 to 336 watts, the average light level increased and amounted to 90 lux, while the  illumination uniformity and color rendition improved. We have developed a resonant power supply system for LEDs to create lighting systems with a «sunrise - sunset» function. (Conclusions)  We have shown the possibility and provided examples of using the developed by us energy-saving controlled lighting systems based on LED light sources.